USE AND EFFECT OF MOVIE TO IMPROVE STUDENTS 'SPEAKING SKILLS - Al Hasan, Layya Aisah; Nur, Dedi Rahman ((JELE) Journal Of English Language and Education, 2021)
Currently, many teachers use movie as learning media or teaching materials for students to learn. Movie are very good for improving language skills in students, especially speaking skills because movie are equipped with audio visuals where in the movie students can hear and see firsthand how the correct words and sentences are pronounced so that students can know how to pronounce them and they can also practice it when talking to people other. This study uses qualitative methods and the sample is 10 students from several universities in Samarinda. They will fill out a questionnaire to find out how students respond to the use of movie as a medium or teaching material and whether they realize that watching movies will improve their speaking skills. The results showed that teachers who use movie as a medium or teaching material, teaching and learning activities become more fun and they get new experiences in learning. They also realized that by watching movies their speaking ability improved because they knew a lot about the correct pronunciation of words and they also knew a lot of new vocabulary.Â